Optimization Extraction of ET-743 from Sea Squirt by Response Surface Methodology and Preparative Chromatographic Separation - Tian, M.; Tang, B.; Row, K.H. (Asian Journal of Chemistry, 2011)
ET-743 is one of the most original anti-tumoral activity compounds from sea squirt. The liquidliquid extraction is widely used to obtain the target compound directly. Response surface methodology was used to predict the extraction conditions. The preparative chromatography was also applied to purify the target compound from extract. The optimized condition (acetone/ methanol (86.67:13.33, v/v), liquid/solid ratio: 8.6 mL/g and 126.0 min dipping time) were estimated using the model equation. 6.47 × 10-4 mg/g of ET-743 can be extracted. By using preparative HPLC column, 5.82 × 10-6 mg of ET-743 was obtained from 1 mL extract. Then, the preparative chromatography with large size of HPLC column was successfully applied to purify the ET-743 from the extract.